$F=[D'+AB'+A'C+AC'D+A'C'D]'$
$F'=D'+AB'+A'C+AC'D+A'C'D$
$F'=1.D'+AB'.1+A'.1C+A.1C'D+A'.1C'D$
$F'=(A+A')D'+AB'(C+C')+A'(B+B')C+A(B+B')C'D+A'(B+B')C'D$
$F'=AD'+A'D'+AB'C+AB'C'+A'BC+A'B'C+ABC'D+AB'C'D+A'BC'D+A'B'C'D$
$F'=A.1D'+A.1'D'+AB'C.1+AB'C'.1+A'BC.1+A'B'C.1+ABC'D+AB'C'D+A'BC'D+A'B'C'D$
$F'=A(B+B')D'+A'(B+B')D'+AB'C(D+D')+AB'C'(D+D')+A'BC(D+D')+A'B'C(D+D')+ABC'D+AB'C'D+A'BC'D+A'B'C'D$
$F'=ABD'+AB'D'+A'BD'+A'B'D'+AB'CD+AB'CD'+AB'C'D+AB'C'D'+A'BCD+A'BCD'+A'B'CD+A'B'CD'+ABC'D+AB'C'D+A'BC'D+A'B'C'D$
$F'=AB.1D'+AB'.1D'+A'B.1D'+A'B'.1D'+AB'CD+AB'CD'+AB'C'D+AB'C'D'+A'BCD+A'BCD'+A'B'CD+A'B'CD'+ABC'D+AB'C'D+A'BC'D+A'B'C'D$
$F'=AB(C+C')D'+AB'(C+C')D'+A'B(C+C')D'+A'B'(C+C')D'+AB'CD+AB'CD'+AB'C'D+AB'C'D'+A'BCD+A'BCD'+A'B'CD+A'B'CD'+ABC'D+AB'C'D+A'BC'D+A'B'C'D$
$F'=ABCD'+ABC'D'+AB'CD'+AB'C'D'+A'BCD'+A'BC'D'+A'B'CD'+A'B'C'D'+AB'CD+AB'CD'+AB'C'D+AB'C'D'+A'BCD+A'BCD'+A'B'CD+A'B'CD'+ABC'D+AB'C'D+A'BC'D+A'B'C'D$
Remove similar tearm,because $[X+X=X]$
$F'=ABCD'+ABC'D'+AB'CD'+AB'C'D'+A'BCD'+A'BC'D'+A'B'CD'+A'B'C'D'+AB'CD+AB'C'D+A'BCD+A'B'CD+ABC'D+A'BC'D+A'B'C'D$
Apply both side complement
$(F')'=[ABCD'+ABC'D'+AB'CD'+AB'C'D'+A'BCD'+A'BC'D'+A'B'CD'+A'B'C'D'+AB'CD+AB'C'D+A'BCD+A'B'CD+ABC'D+A'BC'D+A'B'C'D]'$
Apply Demorgan's laws
$(A+B)'=A'.B'$
$(A.B)'=A'+B'$
$F=(A'+B'+C'+D).(A'+B'+C+D).(A'+B+C'+D).(A'+B+C+D).(A+B'+C'+D).(A+B'+C+D).(A+B+C'+D).(A+B+C+D).(A'+B+C'+D').(A'+B+C+D').(A+B'+C'+D').(A+B+C'+D').(A'+B'+C+D').(A+B'+C+D').(A+B+C+D')$ $[(X')'=X]$
This is Canonical Product Of Sum Term(Maxterm)
$1)A'+B'+C'+D=1110=14$
$2)A'+B'+C+D=1100=12$
$3)A'+B+C'+D=1010=10$
$4)A'+B+C+D=1000=8$
$5)A+B'+C'+D=0110=6$
$6)A+B'+C+D=0100=4$
$7)A+B+C'+D=0010=2$
$8)A+B+C+D=0000=0$
$9)A'+B+C'+D'=1011=11$
$10)A'+B+C+D'=1001=9$
$11)A+B'+C'+D'=0111=7$
$12)A+B+C'+D'=0011=3$
$13)A'+B'+C+D'=1101=13$
$14)A+B'+C+D'=0101=5$
$15)A+B+C+D'=0001=1$
$F(A,B,C,D)=\prod (1,2,3,4,5,6,7,8,9,,10,11,12,13,14)$
$F(A,B,C,D)=\sum (15)$
$$ \textbf{(OR)}$$
Let's First Simplify it
$F=[D'+AB'+A'C+AC'D+A'C'D]'$
$F=[D'+AB'+A'C+C'D(A+A')]'$
$F=[D'+AB'+A'C+C'D.1]'$ $[A+A'=1]$
$F=[D'+AB'+A'C+C'D]'$
$F=(D')'.(AB')'.(A'C)'.(C'D)'$ [ Using Demorgan's Law$: (A+B)=A'.B'$ $(or)$ $(A.B)'=A'+B' ]$
$F=(D).(A'+B).(A+C').(C+D')$ [Again using Demorgan's law ]
$F=(A'D+BD).(AC+AD'+C'C+C'D')$ [Simple multiply]
$F=(A'D+BD).(AC+AD'+0+C'D')$ $[C.C'=0]$
$F=(A'D+BD).(AC+AD'+C'D')$
$F=(A'D.AC+A'D.AD'+A'D.C'D'+BD.AC+BD.AD'+BD.C'D')$
$F=ABCD$ $[A.A'=0,D.D'=0]$
$$\textbf(OR)$$
Let $f(A,B,C,D) = \bigg[D'+AB'+A'C+AC'D+A'C'D\bigg]'$
$\implies \bigg[D'+AB'+A'C+C'D\bigg]'$
$\implies \bigg[D'+C'+ AB' + A'C\bigg]'$
$\implies \bigg[D'+C'+A'+ AB'\bigg]'$
$\implies \bigg[D'+C'+A'+ B'\bigg]'$
$\implies ABCD$
So the number of min-terms$=1$